Supporting GHG Mitigation Actions with Effective Data Management Systems - Partnership for Market Readiness (World Bank, Washington, DC, 2015)
The Partnership for Market Readiness (PMR) is a global partnership, which provides funding and technical assistance to support the design and development of market-based instruments to reduce greenhouse gas (GHG) emissions. The PMR is country-led and builds on countries own mitigation priorities. It emphasizes improving technical and institutional capacity to scale up mitigation efforts, including domestic emissions trading, crediting mechanisms and carbon taxes, among others. The report contains three parts. First, it provides an overview of the types of data management systems included in this analysis, namely, systems that support: (1) national level inventories, (2) facility-level reporting, and (3) carbon asset registries as well as other systems for clean energy and energy efficiency policies. The first part also provides a snapshot of four cases studies (the United Kingdom, Australia, the United States, Germany; Annexes to this report includes full descriptions of the case studies). Secondly, the report presents lessons learned from the case studies, and derives a number of key considerations for designing and developing data management systems. Finally, it proposes design principles that PMR partner countries may find useful when implementing GHG data management systems of their own.